Extracellular vesicles from chronic lymphocytic leukemia cells promote leukemia aggressiveness by inducing the differentiation of monocytes into nurse‐like cells via an RNA‐dependent mechanism - Nathan Dubois; David Van Morckhoven; Laurentijn Tilleman; Filip Van Nieuwerburgh; Dominique Bron; Laurence Lagneaux; Basile Stamatopoulos (HemaSphere)
Abstract Chronic lymphocytic leukemia (CLL) cells receive several stimuli from surrounding cells, such as B‐cell receptor (BCR) stimulation, and can manipulate their microenvironment via extracellular vesicle (EV) release. Here, we investigated the small RNA content (microRNA and YRNA) of CLL‐EVs from leukemic cells cultured with/without BCR stimulation. We highlight an increase of miR‐155‐5p, miR‐146a‐5p, and miR‐132‐3p in EVs and in cells after BCR stimulation (p < 0.05, n = 25). CLL‐EVs were preferentially internalized by monocytes (p = 0.0019, n = 6) and able to deliver microRNAs and the hY4 RNA. Furthermore, BCR CLL‐EV induced modifications in monocytes (shape change, microRNA and gene expression, secretome) suggesting nurse‐like cell (NLC) differentiation, the tumor‐associated macrophages of CLL. Functionally, monocytes treated with BCR CLL‐EVs protect CLL cells from spontaneous apoptosis by pro‐survival cytokine production and induce their migration as well as the migration of other immune cells. We finally reported by transfection experiments that hY4 is able to induce the expression of CCL24, a key gene in M2 macrophage differentiation. In conclusion, we showed that BCR stimulation modifies the small RNA content of CLL‐EVs and that the addition of leukemic EVs to monocytes leads to monocyte differentiation into NLCs establishing a protective microenvironment that supports leukemic cell survival.